Gorham’s Disease of the Mandible - Rathy Ravindran; Anila Karunakaran (Case Reports in Dentistry)
Gorham’s disease is a rare condition characterized by progressive osteolysis of bone with ultimate total disappearance of bone. The aetiology is undetermined. It may affect any bone of the body, although there is predilection for the pelvis, humerus, axial skeleton, and mandible. Because of the rarity, the disorder goes unrecognized. Various treatment modalities are undertaken with very limited success. We report a case of Gorham’s disease of mandible in a 62-year-old man and the literature is reviewed with emphasis on aetiology, diagnosis management.